Acculturation and Mental Health Across Immigrant, Refugee, and International Student Populations: A Bibliometric–Systematic Review - Habibie, Alfiesyahrianta; Lubis, Hairani; Suhesty, Aulia; Handayani, Nanik; Aulia Sari, Rika (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Acculturation research has grown from a niche interest within cross-cultural psychology into a recurring reference point for clinicians and educators working with mobile populations. This review combines bibliometric mapping with a systematic synthesis of studies linking acculturation to mental health outcomes among immigrants, refugees, ethnic minorities, and international students. A Scopus search covering 2016–2026 yielded 65 records; after we screened these against PICo eligibility criteria, 49 empirical studies remained for analysis. Publication output rose sharply after 2023, with the United States anchoring nearly two-thirds of the corpus and Cultural Diversity and Ethnic Minority Psychology serving as the field's most frequent outlet. Keyword co-occurrence patterns cluster around three recurring mechanisms: acculturative stress as a proximal risk factor for depressive and anxious symptoms, ethnic or bicultural identity integration as a buffering resource, and discrimination as a contextual amplifier that interacts with both. Findings further show that outcomes for the same acculturation orientation diverge by generational status, migration circumstance (voluntary versus forced), and host-society receptiveness, indicating that no single acculturation strategy is uniformly protective. Organizations serving immigrant-origin populations, from universities to mental health services, should treat acculturation as a multidimensional and context-dependent process rather than a single score to be optimized.Penelitian akulturasi telah berkembang dari minat khusus dalam psikologi lintas budaya menjadi titik rujukan berulang bagi klinisi dan pendidik yang bekerja dengan populasi mobil. Tinjauan ini menggabungkan pemetaan bibliometrik dengan sintesis sistematis atas studi-studi yang mengaitkan akulturasi dengan luaran kesehatan mental pada imigran, pengungsi, minoritas etnis, dan mahasiswa internasional. Pencarian Scopus yang mencakup 2016–2026 menghasilkan 65 rekaman; setelah kami menyaringnya menggunakan kriteria kelayakan PICo, tersisa 49 studi empiris untuk dianalisis. Jumlah publikasi meningkat pesat setelah 2023, dengan Amerika Serikat menjadi pusat hampir dua pertiga korpus dan Cultural Diversity and Ethnic Minority Psychology sebagai outlet paling sering di bidang ini. Pola ko-occurence kata kunci mengelompok pada tiga mekanisme yang berulang: stres akulturatif sebagai faktor risiko proksimal untuk gejala depresi dan kecemasan, integrasi identitas etnis atau bikultural sebagai sumber daya penyangga, dan diskriminasi sebagai penguat kontekstual yang berinteraksi dengan keduanya. Temuan lebih lanjut menunjukkan bahwa luaran untuk orientasi akulturasi yang sama dapat berbeda berdasarkan status generasi, kondisi migrasi (sukarela versus terpaksa), dan keterbukaan masyarakat penerima, yang mengindikasikan bahwa tidak ada satu strategi akulturasi yang secara universal protektif. Organisasi yang melayani populasi dengan latar belakang imigran, mulai dari universitas hingga layanan kesehatan jiwa, seharusnya memperlakukan akulturasi sebagai proses multidimensional dan bergantung konteks, bukan sebagai satu angka yang harus dioptimalkan.